The Effect of Profitability and Leverage on Sustainability Reporting and It Is Impact on Earnings Informativeness - Bisma, Muhamad; Uzliawati, Lia; Mulyasari, Windu (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to examine the effect of profitability and leverage on sustainability reporting and it impacts on earning informativeness on the Indonesia Stock Exchange 2018-2022. This study takes the mining sector because this sector is the sectors that contribute to Non-Tax State Revenue. The sampling technique used in this study is the purposive sampling method. The data analysis technique of this study uses multiple regression analysis and simple regression analysis. The results of this study prove that profitability (ROA) and leverage (DER) have a negative and significant effect on sustainability reporting (SRDI). besides, sustainability reporting (SRDI) has a positive and significant effect on earning informativeness (ERC).